Pine Ridge Reservation Student Drop-Out Rate and its Contributing Factors - Malec, Kristina (My University, 2013)
Utilizing a mixed-methods approach, the purpose of this study was to compare statistics between the nationwide Native American student dropout rate and the student dropout rate on the Pine Ridge Indian Reservation in South Dakota. Causation factors between the two groups were also compared.
Color poster with text, maps, charts, photographs, images, and tables.
Keywords: Dropout rates; Pine Ridge Indian Reservation (S.D.)--High school students; Native American students (High school); Posters